2012
DOI: 10.1148/radiol.12111883
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort–Echo Time MR Imaging of the Patella with Bicomponent Analysis: Correlation with Histopathologic and Polarized Light Microscopic Findings

Abstract: Purpose:To correlate short and long T2* water fractions, derived from ultrashort-echo time (TE) magnetic resonance (MR) imaging, with semiquantitative histopathologic and polarized light microscopic (PLM) assessment of human cadaveric patellae cartilage. Materials and Methods:Twenty human cadaveric patellae were evaluated by using ultrashort-TE imaging, spin-echo imaging, histopathologic analysis, and PLM, with institutional review board approval. Short and long T2* water components were evaluated for each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 37 publications
6
64
1
Order By: Relevance
“…Furthermore, if applied on the basis of a gradient-echo sequence, it could allow for multiecho imaging with a high image resolution at a rather short acquisition time. 17,28 In theory, T 2 * imaging is prone to signal loss owing to susceptibility-induced artefacts. Therefore, recent publications raised the evidence that using an ultrashort echo time sequence, T 2 * measurement might allow for the detection of early signs of degeneration, such as cartilage microcalcification in close proximity to the bone-cartilage interface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if applied on the basis of a gradient-echo sequence, it could allow for multiecho imaging with a high image resolution at a rather short acquisition time. 17,28 In theory, T 2 * imaging is prone to signal loss owing to susceptibility-induced artefacts. Therefore, recent publications raised the evidence that using an ultrashort echo time sequence, T 2 * measurement might allow for the detection of early signs of degeneration, such as cartilage microcalcification in close proximity to the bone-cartilage interface.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of significant MUSCULOSKELETAL IMAGING: Articular Cartilage of the Human Knee Joint Liu et al times of Carr-Purcell-Meiboom-Gill techniques currently used for multicomponent T2 mapping. Multicomponent T2*-mapping techniques have been used to assess the fast and slow-relaxing water components of human articular cartilage (50,51). In a previous study (50), authors investigated multicomponent T2* parameters of human cadaveric patellar cartilage specimens and showed an increased F F in degenerative cartilage, which the authors attributed to greater binding between water and degraded collagen fibers.…”
Section: Musculoskeletal Imaging: Articular Cartilage Of the Human Knmentioning
confidence: 99%
“…Multicomponent T2*-mapping techniques have been used to assess the fast and slow-relaxing water components of human articular cartilage (50,51). In a previous study (50), authors investigated multicomponent T2* parameters of human cadaveric patellar cartilage specimens and showed an increased F F in degenerative cartilage, which the authors attributed to greater binding between water and degraded collagen fibers. However, multicomponent T2*-mapping techniques use extremely short echo times which can detect signal from the extremely fast-relaxing water tightly bound to the collagen component of cartilage.…”
Section: Musculoskeletal Imaging: Articular Cartilage Of the Human Knmentioning
confidence: 99%
“…173,174 Whether the short T2* component corresponds exclusively to collagen-bound water 174 or to water bound to both collagen and proteoglycan remains unknown. 177 Enzymatic degradation of cartilage has been shown to cause a decrease in the short T2* relaxation time with no change in the long T2* relaxation time. 174 However, another study comparing UTE T2* parameters with histology and polarized light microscopy has found that cartilage degeneration has no influence on the short T2* relaxation time but increases the long T2* relaxation time.…”
Section: Ultrashort Echo Time Imagingmentioning
confidence: 99%
“…This study has also shown that the fraction of the short T2 component has the strongest correlation with the degree of cartilage degeneration and disruption of the collagen fiber network. 177 It has been speculated that the higher fraction of the short T2 component in degenerative cartilage is caused by disruption of the collagen fiber network, which results in increased surface area on the collagen fiber for water binding. However, further studies are needed to better understand the mechanisms responsible for changes in UTE T2* parameters at various stages of cartilage degeneration.…”
Section: Ultrashort Echo Time Imagingmentioning
confidence: 99%